Speed of adjustment towards target capital structure: Southeast Asia evidence - Haron, Razali; Ibrahim, Khairunisah (s.n, 2012)
This study investigates on the existence of target capital structure and speed of adjustment towards the target for firms in the selected Southeast Asia countries covering Malaysia, Thailand and Singapore. Falls under the dynamic aspect of capital structure, a relatively new area in the finance literature this study found the existence of target capital structure among firms in the region and it's a function of several firm and country levels determinants. The speed of adjustment to target leverage varies between firm in the three countries and firms in the region are found to be under-adjust in the sense that they fall short of the adjustment required to attain the target leverage levels